Sistem Tata Kelola Tagihan Pembayaran Klaim Jaminan Kecelakaan Kerja Pada BPJS Ketenagakerjaan Cabang Surabaya Karimunjawa - Melinda Wahyuning Putri; Nurul Azizah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
BPJS Employment cooperates with many employer companies and Work Accident Service Centers in managing Work Accident Insurance. In its management, of course, the company must have an effective and efficient governance system. The research entitled